A systematic approach for ERP implementation in the construction industry - Hadidi, Laith; Assaf, Sadi; Alkhiami, Adel (Journal of Civil Engineering and Management, 2017)
The objective of this paper is to provide a decision support tool that helps in prioritizing enterprise resource planning (ERP) modules’ implementation. The literature shows high risks of failure during the ERP implementation in construction industry. This research provides a systematic approach to have a successful ERP implementation in the construction industry. The provided approach of this research helps construction companies worldwide and specifically Saudi Arabia to better implement ERP projects. A case study approach is conducted with experts in ERP implementation at construction field in order to rank different ERP modules. This research develop a four step methodology to sequence the ERP module implementation. The first step defines the most common ERP modules in the construction industry. The second step defines the expected benefits of ERP implementation. The third step will define the importance index (I). Finally, the fourth step rank the ERP modules based on the global index that combines the criteria index and module index. The main findings of this research provided a comprehensive list of thirteen ERP modules ranked according to the Saudi construction industry. Out of thirteen modules, the top ranked modules were inventory control and logistics, procurement, and project finance and accounting.